Vitamin A, systemic T-cells, and the eye: Focus on degenerative retinal disease - Thirunavukarasu, Arun J.; Ross, A. Catharine; Gilbert, Rose M. (Frontiers in Nutrition, 2022)
The first discovered vitamin, vitamin A, exists in a range of forms, primarily retinoids and provitamin carotenoids. The bioactive forms of vitamin A, retinol and retinoic acid, have many critical functions in body systems including the eye and immune system. Vitamin A deficiency is associated with dysfunctional immunity, and presents clinically as a characteristic ocular syndrome, xerophthalmia. The immune functions of vitamin A extend to the gut, where microbiome interactions and nutritional retinoids and carotenoids contribute to the balance of T cell differentiation, thereby determining immune status and contributing to inflammatory disease around the whole body. In the eye, degenerative conditions affecting the retina and uvea are influenced by vitamin A. Stargardt’s disease (STGD1; MIM 248200) is characterised by bisretinoid deposits such as lipofuscin, produced by retinal photoreceptors as they use and recycle a vitamin A-derived chromophore. Age-related macular degeneration features comparable retinal deposits, such as drusen featuring lipofuscin accumulation; and is characterised by parainflammatory processes. We hypothesise that local parainflammatory processes secondary to lipofuscin deposition in the retina are mediated by T cells interacting with dietary vitamin A derivatives and the gut microbiome, and outline the current evidence for this. No cures exist for Stargardt’s or age-related macular degeneration, but many vitamin A-based therapeutic approaches have been or are being trialled. The relationship between vitamin A’s functions in systemic immunology and the eye could be further exploited, and further research may seek to leverage the interactions of the gut-eye immunological axis.